Highly Thermoconductive, Strong Graphene-Based Composite Films by Eliminating Nanosheets Wrinkles - Xiao, Guang; Li, Hao; Yu, Zhizhou; Niu, Haoting; Yao, Yagang (Nano-Micro Letters, 2023)
Graphene-based thermally conductive composites have been proposed as effective thermal management materials for cooling high-power electronic devices. However, when flexible graphene nanosheets are assembled into macroscopic thermally conductive composites, capillary forces induce shrinkage of graphene nanosheets to form wrinkles during solution-based spontaneous drying, which greatly reduces the thermal conductivity of the composites. Herein, graphene nanosheets/aramid nanofiber (GNS/ANF) composite films with high thermal conductivity were prepared by in-plane stretching of GNS/ANF composite hydrogel networks with hydrogen bonds and π–π interactions. The in-plane mechanical stretching eliminates graphene nanosheets wrinkles by suppressing inward shrinkage due to capillary forces during drying and achieves a high in-plane orientation of graphene nanosheets, thereby creating a fast in-plane heat transfer channel. The composite films (GNS/ANF-60 wt%) with eliminated graphene nanosheets wrinkles showed a significant increase in thermal conductivity (146 W m−1 K−1) and tensile strength (207 MPa). The combination of these excellent properties enables the GNS/ANF composite films to be effectively used for cooling flexible LED chips and smartphones, showing promising applications in the thermal management of high-power electronic devices. Highlights: 1 Highly thermally conductive composite films with elimination of graphene nanosheet wrinkles prepared by a constrained drying strategy of in-plane stretching. 2 Reveals the mechanism of graphene nanosheet wrinkle elimination to improve the thermal conductivity of composite films and demonstrates its use as a heat sink film for cooling flexible LED chips and smartphones.